2018
DOI: 10.2147/cmar.s155524
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastasis pattern in initial metastatic breast cancer: a population-based study

Abstract: PurposeBone is one of the most common sites of breast cancer metastasis, and population-based studies of patients with bone metastasis in initial metastatic breast cancer (MBC) are lacking.Materials and methodsFrom 2010 to 2013, 245,707 breast cancer patients and 8901 patients diagnosed with initial bone metastasis were identified by Surveillance, Epidemiology, and End Results database of the National Cancer Institute. Multivariate logistic and Cox regression were used to identify predictive factors for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
100
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 34 publications
3
100
0
4
Order By: Relevance
“…Patients with cancer of the uterine cervix have been reported to have a relatively lower incidence of bone metastases when compared with cancer of the breast, lung, and prostate [ 17 19 ]. The present study showed that 2.42% of the study cohort of women with cervical cancer had bone metastases when initially diagnosed, which was a similar finding to that of the study conducted by Thanapprapasr et al (1.1%) [ 6 ], but was lower than that found in other studies [ 8 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with cancer of the uterine cervix have been reported to have a relatively lower incidence of bone metastases when compared with cancer of the breast, lung, and prostate [ 17 19 ]. The present study showed that 2.42% of the study cohort of women with cervical cancer had bone metastases when initially diagnosed, which was a similar finding to that of the study conducted by Thanapprapasr et al (1.1%) [ 6 ], but was lower than that found in other studies [ 8 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Surveillance, Epidemiology, and End Results (SEER) program of the National Cancer Institute (NCI) was established in 1973, which includes approximately 30% of the total US population and provides an important data source for epidemiologic analysis [ 17 ]. Therefore, the aims of this study were to analyze the SEER database to determine the incidence and the risk factors for bone metastases in women with bone metastases on initial diagnosis of uterine cervical cancer, and to determine the overall survival, prognosis, and risk factors for patients who present with cervical cancer associated with bone metastases.…”
Section: Introductionmentioning
confidence: 99%
“…The skeleton is the most common site of metastasis in breast cancer patients [ 36 ]. Patients with skeletal metastasis are more sensitive to systemic therapy and have relatively better outcomes than patients with metastasis to other sites [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is a severe threat to the survival of breast cancer patients worldwide [1,2], and bone metastasis occurs in approximately 65% of advanced breast cancer patients. Patients with bone metastasis suffer from bone pain, pathological fractures, hypercalcemia, and spinal cord compression, and the five-year survival rate is about 20% [3,4]. Conventional therapeutic approaches against bone metastasis include radiotherapy, chemotherapy, targeted therapy, endocrine therapy, and bone-modulating drug therapy.…”
Section: Introductionmentioning
confidence: 99%